2016
DOI: 10.1037/lhb0000209
|View full text |Cite
|
Sign up to set email alerts
|

Evidentiary, extraevidentiary, and deliberation process predictors of real jury verdicts.

Abstract: In contrast to the extensive literature based on mock jurors, large-sample studies of decision making by real juries are relatively rare. In this field study, we examined relationships between jury verdicts and variables representing 3 classes of potential determinants-evidentiary, extraevidentiary, and deliberation process-using a sample of 114 criminal jury trials. Posttrial data were collected from 11 presiding judges, 31 attorneys, and 367 jurors using a Web-based questionnaire. The strength of the prosecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Various extra-evidentiary factors can bias the outcome of juror decisions.The most prominently studied of these biasing factors include racial or cultural prejudices and stereotypes. For example, a number of studies have focused on the effects of race and gender on convictions in the criminal justice system (Anwar et al, 2012;Devine et al, 2016;Flanagan, 2018). Experimental evidence compliments this research.…”
mentioning
confidence: 53%
“…Various extra-evidentiary factors can bias the outcome of juror decisions.The most prominently studied of these biasing factors include racial or cultural prejudices and stereotypes. For example, a number of studies have focused on the effects of race and gender on convictions in the criminal justice system (Anwar et al, 2012;Devine et al, 2016;Flanagan, 2018). Experimental evidence compliments this research.…”
mentioning
confidence: 53%
“…The deliberation process includes the style of the discussion that takes place, the individuals or subgroups that offer dissenting views, the number of votes taken, etc. Devine et al (2016) found that the strength of the evidence had the greatest influence on participants, but that extra-evidentiary and deliberation factors might also influence verdicts. Earlier work by Devine et al (2007, p. 300) found that juries did well in some aspects of deliberation but not others.…”
Section: Who Is Being Studied?mentioning
confidence: 94%
“…Further, they state that the research on mock juries has often been conducted with college students (who represent a convenience sample for academics studying jury decision making). Devine, Krouse, Cavanaugh, and Basora (2016) summarized the issue of reliance on college student samples: "Overreliance on studies of undergraduate students making noninteractive decisions about a fictional trial runs the risk of providing a misleading picture of how real juries make decisions. There is a need for more field research that complements and extends the laboratory research with mock jurors" (Devine et al,p.…”
Section: Who Is Being Studied?mentioning
confidence: 99%
“…Participants also completed the survey in isolation, and the group dynamics of jury deliberation were thus not accounted for. This could be a disadvantage, although Devine et al (2016) found that jury deliberation seems to have little impact on the final verdict. It was decided to adopt a Likert scale approach to assessing innocence in order to be able to examine more sophisticated verdict changes.…”
Section: Limitationsmentioning
confidence: 98%